Study of the culture medium variation in the production of secondary metabolite pyrophen by endophytic fungus Aspergillus niger from Harconia speciosa (Research, Society and Development, 2022)
Pyrophen, a natural product, is a pyrone derivative from L-phenylalanine and isolated from different Aspergillus species. This compound exhibits promising anticancer activity, and various studies on its synthesis and biological activity have been reported. Thus, this study aimed to understand the substrate-related factors that influence the production of pyrophen and fungal biomass. So, the endophytic fungus Aspergillus niger, isolated from the plant species Hancornia speciosa (commonly known as mangabeira), was cultivated in different culture media (PDB, CZAPEK, and mangaba juice), ethyl acetate extracts were obtained for these different culture media. A high-performance liquid chromatography method was developed with a PDA detector to quantify pyrophen in these different extracts. This method evaluated the effect of other varying culture media and fungal growth times on the yield of this substance. The highest yield was obtained with the mangaba juice, thus revealing that this medium was better for cultivation. Finally, evaluation of the effect of cultivation time in PDB (Potato Dextrose Broth) medium reveals that the ideal fermentation period to produce pyrophen.